Poor Outcomes in Hepatic Amyloidosis: A Report of 2 Cases - Brandon Yim; Elizabeth Kertowidjojo; Yue Zhang; Pruthvi Patel (Case Reports in Oncological Medicine)
Hepatic amyloidosis is a rare disease entity that results from insoluble amyloid protein deposition in the liver. The disease often presents with vague, nonspecific clinical features. Currently, there is little literature describing treatment outcomes for biopsy-proven hepatic amyloidosis and current treatment guidelines recommend that patients enroll in a clinical trial due to insufficient evidence to suggest an optimal treatment regimen. Here, we present two cases of hepatic amyloidosis at an academic medical center and describe their presentation, treatment, and outcomes. These cases highlight the poor outcomes and difficult management of hepatic amyloidosis. Further understanding and investigation of this rare disease are warranted.